Factor Structure, Construct Validity, and Measurement Invariance of the Neuroception of Psychological Safety Scale (NPSS) - Marta Spinoni; Andrea Zagaria; Anna Pecchinenda; Caterina Grano (MDPI AG, 2024)
Psychological safety has recently emerged as a central construct, strictly implicated in mental health and emotional well-being. The Neuroception of Psychological Safety Scale (NPSS) is the first scale designed to assess feelings of psychological safety from a multidimensional perspective. However, the robustness of its factorial structure requires further examination in large community samples, and evidence of construct validity along with measurement invariance across genders is scarce. The present study aimed to address these gaps through a comprehensive cross-validation approach. A community sample of 660 Italian adults, aged 18-65, completed self-report questionnaires including the NPSS, the Compassionate Engagement and Action Scale (CEAS), the Sussex-Oxford Compassion for Others (SOCS), and the Body Perception Questionnaire (BPQ). A three-factor model, i.e., Social Engagement, Compassion, and Bodily Sensations, demonstrated a good fit to the data in two random subsamples. Moreover, the measurement model was factorially invariant across genders. Model-based omega coefficients supported the internal consistency of the NPSS scores (ω ranged between 0.879 and 0.918). Zero-order correlations between NPSS subscales and CEAS, SOCS, and BPQ provided construct validity evidence. Additionally, inter-correlations between latent factors and Harman's single-factor test supported the discriminant validity of the NPSS dimensions. Overall, this study provided compelling evidence regarding the psychometric properties of the NPSS, demonstrating for the first time the invariance of its factorial structure across gender.